PENGARUH KEPEMIMPINAN TRANSAKSIONAL DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA DAN DAMPAKNYA TEHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN MODERASI KOMITMEN TIM (Jurnal Mahasiswa Pasca Sarjana, 2015)
Ministry of Energy and Mineral Resources (ESDM) and Environmental Agency (BLH) district Rembang will achieve vision, mission, goals and objectives when fully supported by employees as one of the most important assets of Ministry of Energy and Mineral Resources (ESDM) and Environmental Agency (BLH) district Rembang. Furthermore, Organization will not able to achieve its goals without the leadership role. This study aims todetermine the effect of variable transactional leadership against job satisfaction, variable transformational leadership against job satisfaction, variable transactional leadership against organizational citizenship behavior, variable transformational leadership against organizational citizenship behavior, variable job satisfaction against organization citizenship behavior, variable job satisfaction against organization citizenship moderated by team commitment. Population in this study is staff ministry of energy and mineral resources (ESDM) and environmental agency (BLH) district Rembang, which amounted to 85 people and sample collection using census techniques, data collection was done by using a questionnaire and scale SPSS 20.00. Based on research results shows that transactional leadership have significant positive effect against job satisfaction, transformational leadership have significant positive effect against job satisfaction, transactional leadership have significant positive effect against organizational citizenship behavior, transformational leadership have significant positive effect against organizational citizenship behavior, job satisfaction have significant positive effect against organizational citizenship behavior, team commitment weaken the relationship of job satisfaction on organizational citizenship behavior at Ministry Of Energy And Mineral Resources (ESDM) and Environmental Agency (BLH) district Rembang. Suggestion provided to Ministry of Energy and Mineral Resources (ESDM) and Environmental Agency (BLH) district Rembang that is the next leader must apply leadership style which can push up job satisfaction of subordinates, so the employees themselves comfortable in the work and have a high work ethic. Key word: transactional leadership, transformational leadership, job satisfaction, organization citizenship behavior, team commitment